2003
DOI: 10.1021/ac034848s
|View full text |Cite
|
Sign up to set email alerts
|

Isoelectric Point Determination of Norovirus Virus-like Particles by Capillary Isoelectric Focusing with Whole Column Imaging Detection

Abstract: A capillary isoelectric focusing-whole column imaging detection (CIEF-WCID) method was used to determine the isoelectric point (pI) of norovirus virus-like particles (VLPs). The VLPs were produced from noroviruses that represented the two genogroups, genogroup I (Funabashi, Seto, and Norwalk) and genogroup II (Hawaii, Kashiwa, and Narita). Using the imaged CIEF-WCID detection technique, separation was accomplished using a short (4-5 cm) internally coated capillary (100-microm diameter) and a whole-column optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 34 publications
1
68
1
Order By: Relevance
“…The isoelectric pH of NoVs ranges from 5.9 to 6.9 (Goodridge et al 2004). Karim et al (2009) reported that the NanoCeram filter efficiently recovered NoV within a pH range of 6.0 to 9.5.…”
Section: Although Both 1mds Andmentioning
confidence: 99%
“…The isoelectric pH of NoVs ranges from 5.9 to 6.9 (Goodridge et al 2004). Karim et al (2009) reported that the NanoCeram filter efficiently recovered NoV within a pH range of 6.0 to 9.5.…”
Section: Although Both 1mds Andmentioning
confidence: 99%
“…Also, certain porcine SaVs and NoVs are genetically and/or antigenically closely related to the human strains, suggesting the potential for zoonotic infections (40,58,59). Besides the porcine SaV Cowden strain being similar in size (28 to 35 nm) to NoV and having a surface charge range similar to that of NoV (isoelectric points of 5.36 and 5.9 to 6.9, respectively) (21,22), it has been shown recently that porcine SaV shares characteristics similar to those of human NoV, including resistance to low and high pH (42,57), heat (56°C), and chlorine treatments (57). However, unlike human NoV, porcine SaV is culturable, allowing quantification of infectious virus.…”
mentioning
confidence: 99%
“…MNV-1 resistance to independent treatment with LEV or SDS was previously demonstrated with short contact times (Յ5 min) (21). The isoelectric points (pI) of human norovirus capsids are estimated to be between 5.5 and 6.0 for GI and GII norovirus (38), which is similar to the theoretical pI of the Norwalk virus major capsid protein (NCBI accession number M87661.2), estimated to be 5.64 using the ExPASy ProtParam tool (http://web.expasy.org/protparam). The pI of the MNV-1 capsid (NCBI accession number DQ285629.1) has not yet been empirically determined, but it is likely to be similar or slightly lower than the pI of Norwalk virus capsid, since the theoretical pI of the MNV-1 major capsid protein is 4.78 (ProtParam).…”
Section: Discussionmentioning
confidence: 97%